Hemodynamics and Hemorrhagic Transformation After Endovascular Therapy for Ischemic Stroke - Silverman, Andrew; Kodali, Sreeja; Sheth, Kevin N.; Petersen, Nils H. (Frontiers in Neurology, 2020)
Hemorrhagic transformation remains a potentially catastrophic complication of reperfusion therapies for the treatment of large-vessel occlusion ischemic stroke. Observational studies have found an increased risk of hemorrhagic transformation in patients with elevated blood pressure as well as a high degree of blood pressure variability, suggesting a link between hemodynamics and hemorrhagic transformation. Current society-endorsed guidelines recommend maintaining blood pressure below a fixed threshold of 180/105 mmHg regardless of thrombolytic or endovascular intervention. However, given the high recanalization rates with mechanical thrombectomy, it is unclear if the same hemodynamic goals from the pre-thrombectomy era apply. Also, individual patient factors such as the degree of reperfusion, infarct size, and collateral status likely need to be considered. In this review, we will discuss current evidence linking hemodynamics to hemorrhagic transformation after mechanical thrombectomy. In addition, we will review the clinical relevance of cerebral autoregulation in stroke, highlighting recent studies that have harnessed autoregulatory physiology to define and trend individualized limits of autoregulation. This review will go on to emphasize the translatability of this approach to stroke management. Finally, we will discuss novel statistical approaches like trajectory analysis to post-thrombectomy hemodynamics.